2020
DOI: 10.1111/jfb.14245
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition of starry smooth‐hound Mustelus asterias and methodological considerations for assessing the trophic level of predatory fish

Abstract: The stomach contents of 640 starry smooth‐hound Mustelus asterias from the north‐east Atlantic were examined. The diet was dominated by crustaceans (98.8% percentage of index of relative importance, %IRI), with the two main prey species being hermit crab Pagurus bernhardus (34% IRI) and flying crab Liocarcinus holsatus (15% IRI). Ontogenetic dietary preferences showed that smaller individuals [20–69 cm total length (LT) n = 283] had a significantly lower diversity of prey than larger individuals (70–124 cm LT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Dietary studies confirm that M . asterias feed almost exclusively (99% index of relative importance) on crustaceans [ 78 ]. Consequently, time spent near the seabed could be indicative of visual predation, as individuals feed on their benthic and suprabenthic crustacean prey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary studies confirm that M . asterias feed almost exclusively (99% index of relative importance) on crustaceans [ 78 ]. Consequently, time spent near the seabed could be indicative of visual predation, as individuals feed on their benthic and suprabenthic crustacean prey.…”
Section: Discussionmentioning
confidence: 99%
“…Shifts in prey type seem unlikely, as dietary studies have found minimal evidence of mid-water prey in the diet of M . asterias [ 78 ]. Instead, the observed changes in vertical movement behaviour could be indicative of resting or sheltering behaviour during the day, as individuals attempt to avoid potential predators.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, dietary analysis of predators has relied on the morphological identification of undigested remains in feces and stomach contents (e.g., Martins et al, 2011 ; McCully Phillips et al, 2019 ), but this is affected by several key biases. Differences in digestion rates can over‐ or underrepresent some prey, as remains that are resistant to digestion are more likely to be successfully identified (Boyer et al, 2015 ; Pompanon et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%